Research Progress of Hypoxic Tumor Microenvironment in Tumorigenesis - Xu, Nuojie (International Journal of Public Health and Medical Research, 2024)
This article talks about the hypoxic tumour microenvironment (HTM) in several types of tumours, such as ovarian cancer, breast cancer, pancreatic ductal adenocarcinoma, lung cancer, and liver cancer. Researchers have found that hypoxia can make hypoxia-inducible factors (HIFs) work, especially HIF-1α. It is very important for how tumour cells grow, divide, invade, and get away from the defence system. HTM also changes the growth of blood vessels in tumours, the way immune cells work, and how tumour cells get away from immune monitoring. These results show how complicated HTM’s part is in the growth of tumours and point the way to possible targets for the creation of new treatment approaches. Starting from now on, it is very important to fully comprehend how HTM works and how it is controlled. This not only helps to find the deep rule of how tumours grow, but it also encourages the creation of more precise medical treatments for HTM. Some examples are drugs that stop HIF-1α from working properly, treatments that stop tumours from growing new blood vessels, and vaccines that change the immune system’s surroundings. It’s possible that therapy will be used to treat cancer in the future. It was also looked into how HTM affects other factors in the tumour microenvironment, like acidity and interstitial pressure. It will also give us a new way to think about how to treat tumours in a more complete way.